The house on Blueberry Lane - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Catalina Cove., 2022)
"The biggest mistake of Jaye Colfax's life was letting Velvet Spencer leave. For three years, they were together exclusively and it was great--at least for Jaye. But Velvet wanted more ... Tired of waiting, Velvet left him without so much as a goodbye. Only then did Jaye realize he'd been too proud to admit he loved her ... It took Jaye two years to find where Velvet had gone. Now, he's come to Catalina Cove to prove his love and win back her heart. He'll do whatever it takes, even buy the local bank and move in next door"--